Optimum Calcination Temperature In Titanium Dioxide (TiO2) Photocatalyst Coating For Stain-Resistant Fabrics - Fajar Budi Laksono (Multidisciplinary Innovations and Research in Applied Engineering, 2024)
The utilization of wind energy in Indonesia is still low due to the average wind speed ranging from 3 m/s to 11 m/s making it the increasing demand for clothing has driven innovations to address the issue of dirt on clothes in a more practical and environmentally friendly manner. This study explores the use of titanium dioxide (TiO2) as an anti-dirt agent on fabric through a photocatalytic coating process. TiO2 was chosen for its photocatalytic properties, which can oxidize organic compounds into carbon dioxide (CO2) and water (H2O) when exposed to UV light. The fabric coating was carried out using a modified sol-gel method and tested at various calcination temperatures. The optimal result was obtained at a calcination temperature of 600°C, producing anatase crystals with the best photocatalytic properties. Fabric coated with TiO2 showed the ability to degrade stains and kill bacteria after nine coating applications, ensuring an even distribution of TiO2 particles. This study concludes that fabric coated with TiO2 is effective in self-cleaning under UV exposure, offering an environmentally friendly solution suitable for application in sunlight-rich Indonesia.